Emotions in political discourse and social narratives: sociological reflections on traditional and new media - D'Ambrosio, Mariangela (Society Register, 2022)
Emotions have re-emerged as a central topic of sociological interest, especially today, in a complex social and political historical moment. Even politics and events narration is not exempt from the emotional compartment. New technologies and social media (including social networks) have changed communication, relationship processes, and social interaction, moving from a vertical to a horizontal narrative. We live in a “platform society” (Van Dijck, 2018) as online sites and social networks specialized for discussion were also come up with the organization of decision-making processes and the activation of democratic practices in their different “onlife” manifestations. However, one thing should be emphasized: platforms reproduce the social structures in which individuals live between participation, freedom of expression and the elaboration of public political debate. The article aims to synthetically reconstruct the sociological discourse on emotions in political discourse and social narrative and communication through traditional and new media.